Optimizing Coconut Shell Liquid Smoke as A Natural Preservative in Advancing Meatball Production: Optimalisasi Asap Cair Tempurung Kelapa sebagai Pengawet Alami dalam Pengembangan Produksi Bakso - Mutamima, Anisa; Sunarno, Sunarno; Purnama, Indra; Alfarisi, Cory Dian; Fadli, Ahmad; Yenti, Silvia Reni; Barus, Surya Danta Alberto (Universitas Lancang Kuning, 2024)
The Al-Anshar Foundation is an institution currently undertaking various projects and initiatives in the fields of education, social welfare, health, economics, culture, and public health. One of the business units managed by the foundation is the Ikhwan Meatball business, which is currently facing challenges such as limited production and market reach due to the short shelf life of the meatballs produced at room temperature. In this community engagement activity, a team consist of lecturers in the fields of chemical engineering and agriculture, was making efforts to assist the partner in addressing these challenges by equipping them with knowledge and skills to use liquid smoke from coconut shell as a natural preservative in meatball production. The activities included coordination with relevant parties, assistance in liquid smoke production, training on liquid smoke usage, product’s packaging improvement, and monitoring and evaluation. This initiative has yielded positive impacts, including an increase in the partner's skills in producing liquid smoke, a better understanding of the partner regarding the utilization of liquid smoke in meatball production, and an extension of the product's shelf life.